JAVIER RODRÍGUEZ MARCOS, Vida secreta, Barcelona, Tusquets (Col. Nuevos Textos Sagrados), 2015, 75 pp. - Abril, Juan Carlos (Lectura y signo, 2019)
Reseña de JAVIER RODRÍGUEZ MARCOS, Vida secreta, Barcelona, Tusquets (Col. Nuevos Textos Sagrados), 2015, 75 pp.